Measuring environmental factors can enhance the search for disease causing genes?. Issue 7 (11th June 2004) - Dwyer, T; Ponsonby, A-L; Stankovich, J; Blizzard, L; Easteal, S
Abstract : The value of the concurrent measurement of environmental factors in studies aimed at the discovery of disease causing genes has been questioned on the grounds that such an approach fails to increase study power. This report discusses the issue and shows with examples from the recent literature that the examination of a gene disease association within an environmental subgroup can provide enhanced opportunities for detecting gene effects. The concurrent collection of environmental as well as genetic factors in studies of disease aetiology may enhance study informativeness and validity in several ways, including an increase in the power of the study to detect gene disease associations.